Melmon and Morrelli's clinical pharmacology : basic principles in therapeutics - Carruthers, G; Hoffman, Brian B; Melmon, Kenneth L; Morrelli, Howard F (McGraw-Hill. Medical Publishing Division, 2000)
Perfect for the student, primary care practitioner, and pharmacist who needs both basic and clinical information to apply therapeutics A new overview chapter--plus practical steps required for optimal therapeutic decisions Coverage of newly emerging advances in therapeutics A new look at cost/benefit analysis of therapy Increased emphasis on drug interactions, and much more
Keywords: klinická farmakologie; farmacie a farmakologie; farmakoterapie; Drug Therapy; Pharmacology, Clinical